1996
DOI: 10.3382/ps.0750491
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Lactobacillus acidophilus on the Production and Chemical Composition of Hen's Eggs

Abstract: Laying hens were fed for a 48-wk period with a basal diet supplemented with a selected strain of Lactobacillus acidophilus at levels up to four million viable cells per gram of feed. Levels of egg production and feed conversion were significantly higher (8 and 14.8%, respectively) than in the control flock, and cholesterol values in yolks were decreased by 18.8%. It is suggested that the latter effect was a reflection of lower serum cholesterol concentrations in treated birds; a maximum reduction of over 55% f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
49
1
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(72 citation statements)
references
References 13 publications
15
49
1
7
Order By: Relevance
“…These findings are in general agreement with previous studies (Haddadin et al, 1996;Mahdavi et al, 2005) that demonstrated the role of gastrointestinal tract microorganisms in the recycling of lipids. In Japanese quails, Genedy & Zewil (2003) reported a decline in total lipid and cholesterol blood levels of the birds fed a probiotic.…”
Section: Assessment Of a Probiotic Containing Bacillus Subtilis On Thsupporting
confidence: 83%
See 2 more Smart Citations
“…These findings are in general agreement with previous studies (Haddadin et al, 1996;Mahdavi et al, 2005) that demonstrated the role of gastrointestinal tract microorganisms in the recycling of lipids. In Japanese quails, Genedy & Zewil (2003) reported a decline in total lipid and cholesterol blood levels of the birds fed a probiotic.…”
Section: Assessment Of a Probiotic Containing Bacillus Subtilis On Thsupporting
confidence: 83%
“…In the current study, and in agreement with the of Nahashon et al (1996) and Tortuero & Fernandez (1995) in layers, the dietary inclusion of a probiotic containing Bacillus subtilis significantly increased the egg weight of Japanese quails. On the other hand, no effects of such probiotics were found by Haddadin et al (1996) and Chen et al (2009) in layers and Balevi et al (2001) and Yoruk et al (2004) in Japanese quails. These controversial results might be related to probiotic strain, concentration, and Means with different letters within the same column are significantly different (p≤0.05); HDL: High-density lipoprotein; LDL: Low-density lipoprotein; AST: aspartate aminotransferase; ALT: Alanine Aminotransferase, ALP: Alkaline phosphatase; WBC: white blood cell;ND: Newcastle disease antibody titers, AI: Avian influenza antibody titers.…”
Section: Assessment Of a Probiotic Containing Bacillus Subtilis On Thmentioning
confidence: 86%
See 1 more Smart Citation
“…Recently, considerable attention has been given to the potential of probiotics in altering lipid metabolism. This interest stems from the growing evidence that probiotics reduce cholesterol concentration in the egg yolk Haddadin et al, 1996;Panda et al, 2003;Kalavathy et al, 2009) and in the serum (Kurtoglu et al, 2004;Alkhalf et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, probiotic supplementation has been shown to reduce the cholesterol concentration in egg yolk (Abdulrahim et al, 1996;Haddadin et al, 1996) and serum in chicken (Mohan et al, 1996;Jin et al, 1998a). …”
Section: Carcass Quality and Blood Parametersmentioning
confidence: 99%